Can doubt attenuate access to internal states? Implications for obsessive-compulsive disorder. (December 2015) - Lazarov, Amit; Cohen, Tamar; Liberman, Nira; Dar, Reuven
Abstract: Background and objectives: We have previously reported that obsessive-compulsive individuals perform more poorly on tasks that require accurate perception of internal states. As these individuals are also characterized by elevated levels of doubt regarding internal states, the causal relationship between doubt and accurate perception remained unclear. The presented study examines whether undermining participants' confidence in their ability to accurately produce a specific internal state would affect their performance on a task that requires accurate perception of this state. Methods: Participants were trained to produce specific levels of forearm muscle tension and then required to produce various tension levels in four experimental phases. The first three alternated in terms of whether the participants viewed a biofeedback monitor while the fourth offered participants several times the choice to view the monitor. Prior to the task, half of the participants received instructions that undermined their confidence in their ability to accurately assess their own muscle tension. We measured participants' accuracy in producing the required muscle tension levels and the number of times they requested to view the monitor in the final phase. Results: Undermined confidence participants were less accurate in producing the required muscle tension levels in the absence of biofeedback, and were also more likely to request the monitor in the final phase. Conclusions: Doubt can affect performance on tasks that require perceiving and experiencing internal states. This finding supports the possibility that access to internal states in OCD is attenuated due to elevated levels of doubt regarding these states. Highlights: Study explores relationship between doubt and perception of internal states. We manipulated participants' confidence in their assessment of their muscle tension. Undermining confidence impaired accuracy in producing required muscle tension. Doubt can affect performance on tasks that require perceiving internal states. Doubt may attenuate access to internal states in OCD.